2008
DOI: 10.1111/j.1460-9568.2008.06352.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial coordinate systems for tactile spatial attention depend on developmental vision: evidence from event‐related potentials in sighted and congenitally blind adult humans

Abstract: Changes in limb posture (such as crossing the hands) can impair people's performance in tasks such as those involving temporal order judgements, when one tactile stimulus is presented to either hand. This crossed hands deficit has been attributed to a conflict between externally and anatomically anchored reference systems when people localize tactile stimuli. Interestingly, however, the performance of congenitally blind adults does not seem to be affected by crossing the hands, suggesting a default use of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 41 publications
8
78
1
Order By: Relevance
“…Finally, because children were required to perform the Simon and numerical comparison tasks with their hands in parallel or crossed over the body midline, our experiment also allowed us to examine whether low visuospatial skills affect the development of an allocentric spatial frame of reference. According to recent studies, the use of this coordinate system develops during early infancy (Bremner, Holmes, & Spence, 2008) and depends on early visual experience (Collignon, Voss, Lassonde, & Lepore, 2009;Röder, Föcker, Hötting, & Spence, 2008;Röder, Rösler, & Spence, 2004;Röder et al, 2007). Indeed, whereas sighted participants presented classic Simon and SNARC effects in crossed and uncrossed hand conditions, early blind individuals showed the classic effects in the uncrossed condition and showed the reversed effects in the crossed condition (Crollen, Dormal, Seron, Lepore, & Collignon, 2013;Röder et al, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Finally, because children were required to perform the Simon and numerical comparison tasks with their hands in parallel or crossed over the body midline, our experiment also allowed us to examine whether low visuospatial skills affect the development of an allocentric spatial frame of reference. According to recent studies, the use of this coordinate system develops during early infancy (Bremner, Holmes, & Spence, 2008) and depends on early visual experience (Collignon, Voss, Lassonde, & Lepore, 2009;Röder, Föcker, Hötting, & Spence, 2008;Röder, Rösler, & Spence, 2004;Röder et al, 2007). Indeed, whereas sighted participants presented classic Simon and SNARC effects in crossed and uncrossed hand conditions, early blind individuals showed the classic effects in the uncrossed condition and showed the reversed effects in the crossed condition (Crollen, Dormal, Seron, Lepore, & Collignon, 2013;Röder et al, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…In the study by Rôder et al (2008), for instance, congenitally blind and sighted controls had to detect deviant tactile stimuli presented to the index finger of the hand that was cued while adopting either an uncrossed or crossed posture. The results revealed that, consistent with the prediction, the early attentional modulation of tactile ERPs (at 96-120 ms) observed in the uncrossed posture disappeared in the crossedhands posture only for the sighted participants (cf Eimer, Cockburn, Smedley, & Driver, 2001).…”
Section: Auditory Tactile and Audiotactile Spatial Processesmentioning
confidence: 99%
“…Previous evidence suggests that blind individuals represent numerical magnitude along the mental number line: They display the SNARC effect when numbers are presented in the auditory modality and also show other classic properties of normal number representation, such as the distance effect (i.e., longer reaction times when discriminating numerically close quantities, as compared with more distant quantities) (Castronovo & Seron, 2007;Szücs & Csépe, 2005). However, it is not known whether the mental number line, when activated, can influence haptic estimation of external space in blind individuals who usually encode space in body-reference coordinates without generating a visuospatial mental representation (Röder et al, 2008;Röder et al, 2007;Röder et al, 2004). effects observed in the number conditions.…”
Section: Haptic Line Bisection Taskmentioning
confidence: 99%
“…The latter were included in order to investigate whether the possible crossmodal influence of auditorily presented numbers on haptic spatial judgments requires the mediation of a visuospatial mental representation. In fact, there is evidence that crossmodal interactions occur only when sensory information from different modalities is remapped onto an external spatial reference frame, and this may need vision in order to develop (see Collignon, Voss, Lassonde, & Lepore, 2009;Putzar, Goe rendt, Lange, Rösler, & Röder, 2007;Röder, Föcker, Hötting, & Spence, 2008;Röder, Kusmierek, Spence, & Schicke, 2007;Röder, Rösler, & Spence, 2004). Previous evidence suggests that blind individuals represent numerical magnitude along the mental number line: They display the SNARC effect when numbers are presented in the auditory modality and also show other classic properties of normal number representation, such as the distance effect (i.e., longer reaction times when discriminating numerically close quantities, as compared with more distant quantities) (Castronovo & Seron, 2007;Szücs & Csépe, 2005).…”
Section: Haptic Line Bisection Taskmentioning
confidence: 99%